Gravitationally Lensed CO and Dust at High Redshift: New LMT/GTM Images and Spectra of Sub-Millimeter Galaxies. Issue Volume 11:Issue S321(2015) (21st March 2017) - Lowenthal, J. D.; Harrington, K.; Berman, D.; Yun, M.; Cybulski, R.; Wilson, G. W.; Aretxaga, I.; Chavez, M.; De la Luz, V.; Erickson, N.; Ferrusca, D.; Gallup, A.; et al.
Abstract: We have assembled a new sample of some of the most FIR-luminous galaxies in the Universe and have imaged them in 1.1 mm dust emission and measured their redshifts 1 < z < 4 via CO emission lines using the 32-m Large Millimeter Telescope / Gran Telescopio Milimétrico (LMT/GTM). Our sample of 31 submm galaxies (SMGs), culled from the Planck and Herschel all-sky surveys, includes 14 of the 21 most luminous galaxies known, with LFIR > 10 14 L ⊙ and SFR > 10 4 M⊙ /yr. These extreme inferred luminosities – and multiple / extended 1.1 mm images – imply that most or all are strongly gravitationally lensed, with typical magnification μ ~ 10 × . The gravitational lensing provides two significant benefits: (1) it boosts the S / N, and (2) it allows investigation of star formation and gas processes on sub-kpc scales.